The Potential Contribution of Central Banks to Green Finance - Andreas Breitenfellner; Wolfgang Pointner; Helene Schuberth (Vierteljahrshefte zur Wirtschaftsforschung, 2019)
Central banks and financial supervisors approach `green finance' mostly to preserve macroeconomic and financial stability according to their mandates. Obviously, climate change poses severe risks to households, firms and their financial intermediaries. These risks tend to be correlated and their scope goes beyond historical evidence, therefore their impact on the financial system is difficult to model. On the other hand, the planned decarbonization of the global economy creates enormous investment opportunities. Central banks and supervisors play a role in safeguarding the financial system's smooth transformation from funding old, brown industries to funding a new green economy. The `Network for Greening the Financial System' facilitates an exchange of experience and ideas among central banks and financial supervisors; we present some of their findings. While central banks can and should contribute to making the economy and the financial system more sustainable, they can only complement, but not substitute for, decisive political action by governments. – – Zentralbanken und Finanzaufsichtsbehörden haben beim Thema ,,Green Finance“ vor allem die makroökonomische und finanzielle Stabilität im Sinne ihrer Mandate im Blickpunkt. Denn einerseits birgt der Klimawandel erhebliche Risiken für Haushalte, Unternehmen und deren Finanzintermediäre. Diese Risiken sind in der Regel korreliert und ihr Umfang geht über historische Erfahrungswerte hinaus. Daher sind ihre Auswirkungen auf das Finanzsystem schwer zu modellieren. Andererseits schafft die geplante Dekarbonisierung der Weltwirtschaft enorme Investitionsmöglichkeiten. Zentralbanken und Aufsichtsbehörden können zur reibungslosen Umstellung des Finanzsystems zur Finanzierung einer neuen ,,grünen“ Wirtschaft statt alter, ,,brauner“ Industrien beitragen. Das ,,Network for Greening the Financial System“ erleichtert den Erfahrungs- und Ideenaustausch zwischen Zentralbanken und Finanzaufsichtsbehörden. Wir präsentieren hier einige ihrer Erkenntnisse. Trotz ihrer wichtigen Rolle bei der nachhaltigen Gestaltung der Wirtschaft und des Finanzsystems können Zentralbanken entschlossenes politisches Handeln der Regierungen nur ergänzen, nicht jedoch ersetzen.
Keywords: E58; G18; G32; Q54; 330; Central bank policies; government policy and regulation; financial risk and risk management; climate change; natural disasters